Implementasi Dempster Shafer Untuk Deteksi Dini Gizi Buruk Pada Balita - Ridwan Aji Pamungkas; Lilis Dwi Farida (UNIB Press, 2023)
Malnutrition that occurs in toddlers is often caused by an unbalanced intake of nutritious food or caused by certain diseases. Malnutrition is also a cause of digestive disorders in toddlers. Parents who do not understand the problem of malnutrition, make parents not aware of the problems that occur in their children. So, to get accurate and fast information, we need a system that can solve this problem. The dempster shafer method was used in this study to perform early detection of malnutrition in children under five. In this expert system, 3 types of malnutrition can be detected with 23 related symptoms. From the expert accuracy tests that have been carried out, it can be concluded, based on 20 data on early detection of malnutrition in toddlers who have been tested, gives a match rate of 85%. The value of 85% is obtained from the calculation of 17 matching data compared to 20 test data.